Dinamika Pembangunan dalam Kerangka Otonomi Daerah dan Negara Kesejahteraan: Atribut Dominasi terhadap Masyarakat Lokal di Kabupaten Ende - Maximianus Ardon Bidi; Eusabius Separera Niron; Bruno Rey Sonby Pantola; Yohana Fransiska Medho (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2026)
This examines describes the dynamics of development within the framework of regional autonomy as a form of dominant attributes imposed on the local communities in Ende Regency. Using a qualitative approach, the research analyzes the forms of domination exercised through development implementation under regional autonomy and their implications for the realization of welfare-state principles at the local level. The findings reveal a paradox in the paradigm of local development in Ende Regency: the allocation and distribution of resources are imbalanced, with prioritization leaning heavily toward the bureaucratic dimension rather than the community. Based on these findings, community needs at the grassroots level should be prioritized in development, because community-based development cannot be reduced to a merely technocratic process. Ideally, community development should be rooted in the potential and aspirations of local people; in practice however, it is often trapped in rigid bureaucratic and technocratic approaches. This imbalance indicates that development, which should be grounded in local needs, is instead constrained by elitist and exclusive administrative routines that weaken the welfare-state function of regional autonomy.